Performance of hydraulic structures, lifelines and industrial structures during October 30, 2020 Samos-Aegean sea earthquake - Toprak, Selçuk; Uckan, M. Eren; Yilmaz, M. Tolga; Cuceoglu, Faik; Gumusay, M. Umit; Nacaroglu, Engin; Kaya, Ercan S. (Springer, 2022)
This paper presents the effects of October 30, 2020 Samos-Aegean Sea earthquake on hydraulic structures, lifelines and industrial facilities which mainly located in the western cost of Turkey, within the borders of Izmir and Aydin Cities. These two highly populated cities are known for their importance in contributing country's economics by their industrialized areas. In addition, Izmir is the third largest city of Turkey with its high seismic hazard zone. Although some disruptions in the aftermath of the earthquake were occurred in gas and electricity services, these issues immediately identified, and all systems were managed to reoperate. Damages to the infrastructures were mainly due to the collapse of buildings and tsunami effects. No significant damages were reported on lifeline systems, large industrial facilities, and dams due to relatively low shaking intensity.
Keywords: Dams; Industrial facilities; Lifelines; Pipelines